Modeling long-term persistence after 8 years of hepatitis B booster vaccination in 5- to 15-year-old children - Yan Qiu; Zi-Kang Wu; Jie Wu; Jun Yao; Ying Liu; Wen Ren; Yu-Jing Sun; Ling-Zhi Shen; Jing-Jing Ren (Taylor & Francis Group, 2022)
Vaccination remains the most effective and cost-saving measure to protect against hepatitis B, a global health problem. It is crucial to characterize the persistence of the immune response after booster vaccination. This study aimed to quantify the persistence through mathematical modeling. Booster vaccination against hepatitis B was conducted in children 5-15 years in 2009-10 in Zhejiang Province. There were four dosage formulations of hepatitis B vaccines [Shenzhenkangtai Biotechnology Co. Ltd. Dalianhanxin Biotechnology Co. Ltd. NCPC GeneTech Biotechnology Pharmaceutical Co. Ltd. Sinovac Biotech Co. LTD. China]: 5, 10, and 20 μg hepatitis B vaccines or 5 μg hepatitis A and B (HAB) combination vaccine with a 0-1-6-month schedule. These were randomly administered to children negative for all hepatitis B markers, named as the schedule 2 group. Anti-HBs positive subjects were given one dose of booster, named as the schedule 1 group. Anti-HBs antibody was measured 1, 7, 18, 66, and 102 months after the first booster dose. A linear mixed-effects model was proposed to predict long-term persistence. One hundred two months after the booster dose, the mean anti-HBs levels were 33.8 mIU/mL, with 73.7 mIU/mL for the schedule 1 group and 20.2 mIU/mL for the schedule 2 group. The model predicted that 99.5% of subjects would remain seropositive (≥10mIU/mL) at year 20 post booster vaccination, with 100.0% and 98.8% for the schedule 1 group and the schedule 2 group, respectively, whereas at year 30, the seropositivity rates would decrease to 76.8%, with 99.4% for the schedule 1 group and 62.5% for the schedule 2 group. The immunogenicity of the booster vaccination could persist for at least 8 years. Mathematical modeling may predict even longer, up to 30 years of protection.